Status and Challenges of the National Service Training Program and Its Impact on Values Formation - Magbanua, Jose (JPAIR Institutional Research, 2017)
National Service Training Program (NSTP) is a very significant factor in the values formation of students. The study determined the status and challenges of NSTP and its impact on students ' values formation. The respondents were 349 NSTP graduates from school year 2013-2014. A set of researcher-made survey questionnaire was used as tool in data gathering. Frequency, percentage, mean and standard deviation were used a descriptive statistics and Man-Whitney U Test and Kruskal-Wallis H Test at 0.05 alpha were employed as inferential statistics. All statistical computations were processed through the Statistical Package for Social Sciences (SPSS) software. Results showed that the status of NSTP implementation as perceived by students as a whole and when grouped as to sex and program component was "good"and when classified as to course, Fisheries rated "excellent".  As to challenges of NSTP implementation, the Fisheries rated "serious" and when classified as to course, "very serious". The impact of NSTP on students ' values formation as a whole and classified as to variables was "high". No significance difference on the level of challenges was noted when variables were classified into sex and program component but a significant difference as to course. The good values of students at UA are greatly influenced by the program policies of NSTP training.
Keywords: Education; values formation; NSTP training; descriptive design